The study on the soil heat transfer characteristics for the development of a cost-saving underground air cooling system - Din, Abdul Talib; Mohd Zaidi, Zairul Fazura (2011)
The soil heat transfer characteristics are important aspect when dealing with construction in contact with the soil. For example, in order to build a good cool and comfortable home, we should build it floors, walls and ceiling using highest conductivity materials internally and highest insulation material externally. This can also be applied for buried ducting in various type of soils. Buy knowing the thermal effects of the buried pipe, we can predict the consequence of burying different materials of pipe underneath different materials of soil. In this study, the thermal characteristics of various soil types i.e. sand, peat soil, loam soil, powdery soil as external material, combined with the metals i.e Aluminium, stainless steel, carbon steel, copper for internal materials. The test rig is designed such a way that the cross combinations of the above materials can be carried out easily. There are 5 types of soil thermal characteristics were studied in this research, they are peat soil, fine and course sandy soil, loam soil and organic soil. As example the combination of copper pipe with the porous soil or the combination of the carbon steel pipe underneath the lateritic soil. The test results show that with the increase of soil thermal conductivity, the heat in the metal ducting can be drained out faster to the earth hence cooling down the temperature in the ducting. From the thermal conductivity test for six types of soil using proctor test is peat soil and organic soil: 0.4499 W / (m.K), second is stone yellow soil: 0.4424 W / (m.K), following the loam soil: 0.4275 W / (m.K), fine sandy soil: 0.37019 W / (m.K) and coarse sandy soil: 0.349 W / (m.K). The thermal conductivity experiment of six type of soil via laboratory experiment is peat soil: 0.4699 W/mK,